Stereotactic and Functional Neurosurgery Resident Award 189 The Physiology of Heteromodal Proper Naming in the Human Anterior Temporal Lobe. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Abel, Taylor J.; Rhone, Ariane; Nourski, Kirill; Kawasaki, Hiroto; Oya, Hiroyuki; Griffiths, Timothy; Howard, Matthew A.; Tranel, Daniel
Abstract: INTRODUCTION: The anterior temporal lobe (ATL) is a key component of the auditory and visual ventral stream, thought to assign meaning to visual and auditory stimuli. Evidence from neuropsychology and functional neuroimaging demonstrates a critical role for the left ATL in proper noun naming. This is evident after dominant temporal lobectomy, where many patients develop a naming deficit. Despite its importance in naming, due to technical limitations in functional neuroimaging techniques, the physiology of the ATL is poorly understood and clinical language mapping techniques for the ATL are currently unavailable. We sought to describe the physiology of visual and auditory naming in the ATL to lay the groundwork for future clinical mapping techniques. METHODS: Three men undergoing seizure localization with intracranial electrodes (with dense ATL coverage) performed a visual and auditory naming task. Patients named 300 pictures and voice clips of 3 presidents (ie, Barack Obama) and physiologic responses were recorded. Event-related band power (ERBP) was measured for each ATL recording site and compared to fusiform gyrus (FG) and super temporal gyrus (STG) for the visual and auditory naming (Figure 2). The examination of the spectral properties of ATL physiology, the ATL, FG, and STG were divided into anatomical regions of interest (ROI) (Figure 3) and ERBP magnitude plotted as a function of frequency for each ROI (Figure 4). RESULTS: Visual and auditory naming resulted in increased power in low frequencies (4-50 Hz) within the ATL (Figures 2 and 3). The power increase began at 250 milliseconds and peaked at 1 second, with a significant ERBP magnitude for both visual and auditory naming at most ATL sites (Figure 5). CONCLUSION: We provide the first direct evidence for congruent visual and auditory naming physiology in the human ATL. Further understanding of ATL physiology may influence future techniques to map eloquent ATL cortex.